Multiple stressors and benthic harmful algal blooms (BHABs): Potential effects of temperature rise and nutrient enrichment. (June 2018) - Fricke, A.; Pey, A.; Gianni, F.; Lemée, R.; Mangialajo, L.
Abstract: Blooms of Ostreopsis cf. ovata, causing health incidence and mass human intoxications in the Mediterranean, gained special attention over the past decades. To study the potential effects of temperature and nutrient enrichment on this benthic dinoflagellate and other associated microalgae in situ, a multifactorial experiment was set up along a temperature gradient of a heat pump system in Monaco. Microalgae were quantified in experimental units, in the natural biofilm and in the water column. No significant interaction was observed between temperature and nutrients. A species- and bloom phase-dependent effect of the increased temperature was recorded, while the nutrient enrichment had a significant effect only at the end of the experiment (when cell abundances were low). Temperature effects were also visible in the biofilm and the surrounding water. The observed assemblages were mainly driven by changes in abundances of Ostreopsis cf. ovata and Actinocyclus sp., affected in different ways. Graphical abstract: Highlights: An in situ experiment investigated the effect of temperature and nutrients on microphytobenthos, using a heat pump system. Ostreopsis cf. ovata and Actinocyclus sp. were observed on macroalgae with max. values of 1, 040, 000 and 480, 366 cells g FW -1 . Ostreopsis cf. ovata and Actinocyclus sp. reached concentrations of 1940 and 3329 cells/cm 2 on artificial substrates. No significant interaction was observed between temperature and nutrients. Strong temperature effects were visible at different substrates and the surrounding water at different phases of blooms. Nutrient enrichment showed a significant effect only at the end of the experiment.